Cenozoic positive inversion tectonics and its migration in the East China Sea Shelf Basin. (29th April 2016) - Zhang, Guohua; Li, Sanzhong; Suo, Yanhui; Zhang, Jianpei
Abstract: Based on detailed analysis of the inversion tectonics in each of the secondary tectonic units of the East China Sea Shelf Basin (ECSSB), this paper suggests that the Cenozoic positive inversion tectonics in the basin are typically anticlines of various shapes associated with thrusts. Four stages of tectonic inversions are recognized in the basin related to the Oujiang Movement (T80), the Yuquan Movement (T30), the Huagang Movement (T20) and the Longjing Movement (T12), and these four inversion stages are temporally and spatially distinct. Temporally, the tectonic inversion in the West Depression Group tended to weaken, relatively, from the Oujiang Movement (T80) to the Huagang Movement (T20), while the Longjing Movement (T12) does not show an obvious inversion signature. Spatially, the Longjing Movement tectonic inversion in the Xihu and Diaobei sags of the East Depression Group shows a pronounced reduction in intensity from north to south. The tectonic inversion in the East Depression Group tended to intensify, relatively, from the Yuquan Movement (T30), through the Huagang Movement (T20) to the Longjing Movement (T12). The intensity distribution, migration and evolution of Cenozoic inversions in the ECSSB are local responses to the synthetic effect of the convergence and subduction rates, and direction changes between the Pacific and Eurasian plates and/or between the Indian and Eurasian plates. In particular, the eastward migration of positive inversion tectonics in the ECSSB is closely and successively related to the formation of the East Depression Group and the opening of the Okinawa Trough. Copyright © 2016 John Wiley & Sons, Ltd.